Single-Family Houses by Ranko Radović - Gubić, Ilija; Putnik Prica, Vladana (Arhitektura i urbanizam, 2022)
Ranko Radović (1935-2005) was one of the most prominent architects, urban planners and professors in Yugoslavia, and he had a significant impact on professional and scientific discussions on the planning and design of public spaces and public buildings. This is evident not only through his designs, but also through numerous publications and presentations. In addition to his well-known public buildings, such as the Museum at Tjentište in Bosnia and Herzegovina, the Craft Center in Belgrade, the City Hall in Aranđelovac, and the Post Office, Hotel Partizanka and Bank in Vranjačka Banja, he also designed five single-family houses. Of the five houses, four have been built, however, so far, they have not been the focus of research or published in academic journals. This paper studies Ranko Radović’s designs for single-family houses built in the period from 1975 to 1985 in Aranđelovac, Bačka Palanka and Sombor in Serbia. The significance of Radović’s design for single-family houses is explored in the context of socialism, in which investors would choose designs for their houses from a “catalogue”. This paper also explores Radović’s designs in the context of his theoretical approaches on the relationship between traditional and contemporary architecture. The paper aims to shed light on his contribution to ideas regarding the development of modern housing in the 1970s and 1980s in Serbia. It also documents the importance of those projects for the history of the architecture of single-family housing in Serbia.